(untitled) (INNOVATIVE ECONOMY, 2020)
Zheliuk T.L., Onofriichuk D.M. CONCEPTUAL PRINCIPLES OF USING PUBLIC MANAGEMENT IN THE SYSTEM OF PUBLIC ADMINISTRATION Purpose. The aim of the article is consideration of the conceptual foundations of the use of public management tools in modern conditions from the standpoint of strengthening the institutional capacity of government institutions to perform functional activities. Methodology of research. The following general scientific methods are used in the research process: system, structural analysis, grouping ‒ in the study of structural elements of public administration and public management; historical analysis ‒ when considering the scientific foundations of public management; comparative analysis of scientific schools, concepts and models of public management ‒ when choosing basic scientific concepts for the use of levers of public management. Findings. The essential determinants of public management are analysed, the objective necessity of its use in modern practice of public administration is verified. It is substantiated that the effectiveness of state transformations depends on the innovation and modernization of public administration tools. The need to study the best practices and models of public management is established in order to create a conceptual model of new public management for public institutions of the national economy. Originality. The major contradictions in the system of public management and the mechanisms of their solution are systematized. Conceptual approaches to the use of public management in the activities of public institutions as an effective functional innovative tool of public administration are substantiated. Practical value. The results of the study can be the basis for further research on improving approaches to public administration and to create an effective organizational and functional mechanism of public management. Key words: public administration, public management, public administration, theories of new public management, neoliberal theory.